Modernization of Boarding Boards through Digitalization of The Education System in Pensantren - Ah. Shidiq; Muhammad Ufuqul Mubin (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2022)
The process of digitizing the education system of Islamic boarding schools is a creation of Islamic boarding schools in conditions of life or times where all supporting activities are facilitated through technology, especially in the field of administration and learning. This research focuses on digitizing the education system at Pondok Pesantren Darussalam Tegalrejo, Prambontergayang, Soko District, Tuban Regency. A unique context that is natural and by utilizing various natural methods. This type of research uses a descriptive qualitative approach, namely research that intends to understand the phenomena of what is experienced by the research subjects such as behavior, perceptions, motivations, actions and others holistically, and by way of descriptions in the form of words and language. The results showed that at first, the educational activities of the Darussalam Tegalrejo Islamic boarding school in Prambonterga Village were only limited to the recitation of the classic yellow book, then moved further and adjusted to the times in the hope of being able to compete with good quality and quality. The process of digitizing the education system of the Darussalam Tegalrejo Islamic boarding school in Prambonterga Village which includes several aspects, namely: First, digitization in administration and learning, namely from learning activities, it is hoped that students are ready to become competent outcomes in facing future life, and can become human beings, not knowing beings. In addition, the digitalization of administration can support a more effective and efficient administration and filing process.